2021
DOI: 10.1002/ecm.1478
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the consequences of gradual phenotypic plasticity for populations in variable environments

Abstract: Phenotypic adjustments following environmental change are ubiquitous and trait changes arising through phenotypic plasticity often lag behind their environmental stimuli. Evolutionary biologists seeking to understand how adaptive plasticity can evolve have extensively studied this phenomenon. However, the ecological consequences of common features of plastic responses to environmental variability, including gradual phenotypic change (i.e., slower than the pace of environmental change), are underappreciated. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 74 publications
(95 reference statements)
3
44
0
Order By: Relevance
“…Developing a more mechanistic foundation for these patterns and building on prior work in this area (Geider et al 1997, Li et al 2017) would be invaluable. Finally, while our results indicate that photoperiod and photoacclimation can alter the interaction between irradiance and temperature, fluctuations in temperature are also common in nature, introducing the potential complication of thermal acclimation (Kremer et al 2018, Fey et al 2021.…”
Section: Implications For Understanding Phytoplankton Dynamics In Naturementioning
confidence: 73%
“…Developing a more mechanistic foundation for these patterns and building on prior work in this area (Geider et al 1997, Li et al 2017) would be invaluable. Finally, while our results indicate that photoperiod and photoacclimation can alter the interaction between irradiance and temperature, fluctuations in temperature are also common in nature, introducing the potential complication of thermal acclimation (Kremer et al 2018, Fey et al 2021.…”
Section: Implications For Understanding Phytoplankton Dynamics In Naturementioning
confidence: 73%
“…Accordingly, there has been scant consideration of the types of environments in which rates of RPP may be of particular importance. However, several recent contributions have developed verbal predictions describing the types of environments where rates of RPP may be of ecological significance (Fey et al, 2021; Kremer et al, 2018; Pinek et al, 2020). In two of these key papers, these predictions were tested by measuring the growth rate of experimental populations of phytoplankton that differed in initial phenotype (as induced by prior acclimation to different temperatures) and were exposed to different patterns of temperature fluctuation (e.g., temperature could fluctuate in a particular direction or the amplitude or frequency of temperature cycles could vary).…”
Section: The Rate Of Plasticity In An Ecological Settingmentioning
confidence: 99%
“…The environmental domains where the rate of plasticity in population growth held ecological importance were then assumed to be indicated where models that accounted for the rate of plasticity were able to outperform models that either disregarded the rate of plasticity or assumed that it occurred instantaneously. This process of confronting predictions with experimental data indicated that the ecological consequences associated with rates of plasticity likely depend on interactions between the past environments experienced by individuals in a population (because this will influence the ‘initial’ phenotype of those individuals and thus determine how much phenotypic change will be required to produce the new phenotype in the new environment) and the magnitude, frequency and direction of change in the current environment (Fey et al, 2021; Kremer et al, 2018).…”
Section: The Rate Of Plasticity In An Ecological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is usually referred to as phenotypic plasticity. Exploring the mechanism of phenotypic plasticity will help us understand future changes in species distribution and community composition, and manage the forest and crop production [10][11][12]. At present, phenotypic plasticity is a central issue of plant eco-physiological studies [13].…”
Section: Introductionmentioning
confidence: 99%